2005
DOI: 10.1024/0300-9831.75.6.371
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of in vitro Models to Predict the Bioavailability of Iron and Zinc: A Consensus Statement From the HarvestPlus Expert Consultation

Abstract: A combination of dietary and host-related factors determines iron and zinc absorption, and several in vitro methods have been developed as preliminary screening tools for assessing bioavailability. An expert committee has reviewed evidence for their usefulness and reached a consensus. Dialyzability (with and without simulated digestion) gives some useful information but cannot predict the correct magnitude of response and may sometimes predict the wrong direction of response. Caco-2 cell systems (with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 0 publications
2
68
0
1
Order By: Relevance
“…This variation among Lactobacillus sp. has been observed before (14,30). We found that 33% probiotic dairy isolates and 14% pharmaceutical probiotic isolates were poorly adherent.…”
Section: Discussionsupporting
confidence: 60%
“…This variation among Lactobacillus sp. has been observed before (14,30). We found that 33% probiotic dairy isolates and 14% pharmaceutical probiotic isolates were poorly adherent.…”
Section: Discussionsupporting
confidence: 60%
“…These results and the high variability in Caco-2 cell ferritin responses confirm the need to ultimately investigate Fe absorption in humans (48) . Discrepancies in the quantitative assessment between in vitro and in vivo methods assessing Fe bioavailability are well documented and are likely due to factors such as Fe status or dose of administered Fe, which can only be taken into account in in vivo studies (49) . A limitation of the present study was the relatively high variability of Fe concentration in the intrinsically labelled bouillon cubes fortified with FeSO 4 , and this may have increased measurement error in the bioavailability assessment of the FeSO 4 -fortified bouillon cubes.…”
Section: Discussionmentioning
confidence: 99%
“…Both food and host factors influence bioavailability of the nutrients. Bioavailability of nutrients in humans is determined by a sequential series of events, which include (1) digestion and release of elements from food matrix into the lumen of gastrointestinal (GI) tract (availability), (2) transport into intestinal enterocytes (uptake), (3) efflux across the basolateral membrane of enterocytes into the circulation (absorption), (4) retention, or endogenous excretion in urine and feces (retention), (5) transport to tissues for use in normal body functions (utilization), and (6) transport to storage sites (body stores) (Fairweather-Tait et al 2005). Furthermore, Fernandez-Garcıa et al (2009) defined bioavailability as a sum of bioaccessibility and bioactivity and defined bioaccessibility as the fraction of a compound that is released from its matrix in the GI tract and thus becomes available for intestinal absorption.…”
Section: Micronutrient Bioavailabilitymentioning
confidence: 99%
“…Other in vitro methods include solubility and dialyzability that are not useful predictors of iron absorption in comparison to Caco-2 cell model, which provide the most useful in vitro experimental approach for studying iron availability from food digests to predict about the iron bioavailability in vivo. However, further developments are required to optimize and standardize methodologies between different laboratories, including cell type and passage number, cell culture conditions, use of dialysis membranes for food digests that contain ferritin and other large-molecular weight iron complexes, time of exposure to food digest, harvesting of cells, and the use of reference standards so that direct inter-laboratory comparisons can be made between different food substrates (Fairweather-Tait et al 2005). …”
Section: Micronutrient Bioavailabilitymentioning
confidence: 99%